2008
DOI: 10.1182/blood-2007-08-109710
|View full text |Cite
|
Sign up to set email alerts
|

Defective angiogenesis, endothelial migration, proliferation, and MAPK signaling in Rap1b-deficient mice

Abstract: Angiogenesis is the main mechanism of vascular remodeling during late development and, after birth, in wound healing. Perturbations of angiogenesis occur in cancer, diabetes, ischemia, and inflammation. While much progress has been made in identifying factors that control angiogenesis, the understanding of the precise molecular mechanisms involved is incomplete. Here we identify a small GTPase, Rap1b, as a positive regulator of angiogenesis. Rap1b-deficient mice had a decreased level of Matrigel plug and neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
154
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 56 publications
14
154
1
Order By: Relevance
“…The activation of ERK and p38 MAP kinase plays an important role in endothelial cell proliferation and migration (Rousseau et al, 1997;Chrzanowska-Wodnicka et al, 2008;Matsunaga et al, 2008). In addition, the results of the present study showed that RCME inhibited phosphorylation of VEGFR2, resulting in downregulation of ERK and p38 MAP kinase phosphorylation in response to VEGF in HUVECs (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The activation of ERK and p38 MAP kinase plays an important role in endothelial cell proliferation and migration (Rousseau et al, 1997;Chrzanowska-Wodnicka et al, 2008;Matsunaga et al, 2008). In addition, the results of the present study showed that RCME inhibited phosphorylation of VEGFR2, resulting in downregulation of ERK and p38 MAP kinase phosphorylation in response to VEGF in HUVECs (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…In order to identify the downstream signaling pathways targeted by RCME, we next examined the phosphorylation of MAPK, one of the key signaling pathway components that drive endothelial cell proliferation, migration and tube formation (Rousseau et al, 1997;Takahashi et al, 1999;Huang et al, 2004;Chrzanowska et al, 2008). While treatment with RCME inhibited VEGF-dependent phosphorylation of extracellular signal-regulated kinase 1/2 (ERK 1/2) and p38 in a dose-dependent manner, total ERK and p38 levels were not affected ( Figs.…”
Section: Effect Of Rcme On Erk P38 and Vegfr2 Phosphorylationmentioning
confidence: 99%
“…The A2b-Epac1-Rap1B Pathway in the Context of Migration of Cancer Cells-Our discovery of a critical involvement of Rap1B in the positioning of the centrosome and nucleus may explain previous observations that cells isolated from Rap1B-deficient mice display decreased migration (80), that Rap1B knockdown results in impaired cell migration of human endothelial cells (81), and that Rap1B suppression by miR-708 results in inhibition of ovarian cancer cell migration/invasion (83). However, some studies reported a correlation between hypoxia and cell motility in cancer cells, including enhanced metastatic potential (84,85).…”
Section: Discussionsupporting
confidence: 50%
“…Lung endothelial cells isolated from Rap1B-deficient mice display decreased migration in vitro (80). Rap1B knockdown by RNAi in endothelial cells and human umbilical vein endothelial cells results in the same phenotype (81, 82).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Proliferation and migration of ECs has been shown to be an essential criterion for angiogenesis. [27][28][29] We demonstrate active EC proliferation that turns the ischemic hemisphere into a highly plastic vascular system with multiple angiogenic sprouts. The continued angiogenic sprouting results in an increased vessel density in both perilesion and lesion region.…”
Section: Discussionmentioning
confidence: 99%